Pembentukan Mata Uang Tunggal Kawasan ASEAN - Nurul Cholifah; Diah Wahyuningsih (e-Journal Ekonomi Bisnis dan Akuntansi, 2020)
Financial integration is the last step that can be done to achieve economic integration. One condition that must be met before the implementation of financial integration is the existence of the optimal currency area (OCA) criteria. The purpose of this study: 1) to find out the closeness of the currency to changes in the bilateral exchange rate as a supporter in the possibility of forming a single currency in the ASEAN region, 2) to analyze the chosen anchor currency which has a positive influence (appreciation) on the local currency of the ASEAN region as a currency single money region. This study uses annual real output data, size of GDP ratio, bilateral trade, differences in the composition of trade, and the exchange rate throughout of 1995-2018 period. The analytical method used is panel data test. The results showed that the currencies of ASEAN countries did not yet have the closeness of forming a single currency in the ASEAN region. Meanwhile, to determine the appropriate anchor currency to be used as a shared currency, namely SGD (Singapore Dollar) empirically has a positive influence (appreciation) in the ASEAN region compared to RMB, JPY, Euro, or USD. Therefore SGD can be proposed as an anchor currency for ASEAN countries.